1972
DOI: 10.3758/bf03328972
|View full text |Cite
|
Sign up to set email alerts
|

Runway performance of goldfish as a function of complete and incomplete reduction in amount of reward

Abstract: Two experiments are reported in which goldfish failed to show the inverse relation between resistance to extinction and amount of reward and failed also to show the depression effect under conditions analogous to those which most clearly produce these effects in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Some puzzling experiments with goldfish have been reported in which performance was entirely unaffected by a shift from a large to a small reward (e.g. , Gonzalez et al, 1972) but the superior performance of unshifted control animals trained with a large as compared…”
Section: Resultsmentioning
confidence: 99%
“…Some puzzling experiments with goldfish have been reported in which performance was entirely unaffected by a shift from a large to a small reward (e.g. , Gonzalez et al, 1972) but the superior performance of unshifted control animals trained with a large as compared…”
Section: Resultsmentioning
confidence: 99%
“…The wide range of conditions under which successive negative contrast has failed to appear in competent experiments with goldfish (Bitterman 1984;Couvillon & Bitterman 1985;Gonzalez et al 1974;Gonzalez et al 1972;Mackintosh 1971) is hardly suggested by Macphail's "review." Several types of reward have, in fact, been used (Noyes fish pellets, live Tubifex worms, and liquid foods differing in quantity or in quality), and a variety of responses have been measured (starting, swimming, and goal-entry in the runway, striking a target separate from the feeding place, and consummatory responding at a liquid feeder).…”
Section: B6k6sy Laboratory Of Neurobiology University Of Hawaii Honmentioning
confidence: 99%
“…Congruent results obtained in experiments of other designs should be considered as well. Rats extinguish more rapidly after training with large as compared with small reward (Gonzalez & Bitterman 1969;Hulse 1958;Wagner 1961) -a special case of successive negative contrast -but resistance to extinction in goldfish increases with amount of reward (Gonzalez et al 1972); it was an early indication of this difference between rats and goldfish that prompted the Lowes experiment. Successive negative contrast is also a factor in the spacedtrials partial reinforcement effect found in rats trained with large reward (Gonzalez & Bitterman 1969;Hulse 1958;Wagner 1961).…”
Section: B6k6sy Laboratory Of Neurobiology University Of Hawaii Honmentioning
confidence: 99%
“…Gonzalez et al (1974) reviewed a variety of sources of evidence that suggest that goldfish are capable of learning the sensory consequences of responding under optimal conditions; fish show patterning, for example, in single alternation of reward and nonreward if the trials are highly massed and training is extensive. Although no fish contrast experiments have been conducted under identical conditions to those reported by Gonzalez et al (1972) to be effective for aftereffect learning in fish, the reasonable inference drawn from the fish comparisons was that it is doubtful that generalization decrement is the mechanism of successive contrast.…”
Section: Subjectsmentioning
confidence: 99%
“…SuNCE. Reward reduction in goldfish has consistently failed to produce successive contrast (Gonzalez, Ferry, & Powers, 1974;Gonzalez, Potts, Pitcoff, & Bitterman, 1972;Lowes & Bitterman, 1967;Mackintosh, 1971). Gonzalez et al (1974) reviewed a variety of sources of evidence that suggest that goldfish are capable of learning the sensory consequences of responding under optimal conditions; fish show patterning, for example, in single alternation of reward and nonreward if the trials are highly massed and training is extensive.…”
Section: Subjectsmentioning
confidence: 99%